Liver Sinusoidal Endothelial Cells and Regulation of Blood Lipoproteins - Svistounov, Dmitri; Zykova, Svetlana N.; Cogger, Victoria C.; Warren, Alessandra; McMahon, Aisling C.; Fraser, Robin; Couteur, David G. Le (IntechOpen, 2012)
None